TV-Monopoly, Advertising and Program Quality - Rüdiger Pethig (Universität Siegen, Fakultät III, Wirtschaftswissenschaften, Wirtschaftsinformatik und Wirtschaftsrecht, 1993)
A monopolistic advertiser-supported television station chooses the program quality to serve (potential) viewers whose preferences may be skewed towards low or high program quality. The monopolist's profit-maximizing choice of program quality is completely characterized for fixed advertising time and different parameter constellations. The welfare implications of monopolistic supply are investigated, and the market allocation turns out to be significantly biased with the size and direction of allocative displacement depending on the values of demand and supply parameters. In some cases monopoly is shown to undersupply program quality, while under different parameter constellations the monopolistic program quality is greater than the welfare-maximizing one.
Keywords: 330